Biomechanics in clinical orthodontics - Nanda, Ravindra (W.B. Saunders, 1997)
This state-of-the-art resource is the first book to describe how the principles of biomechanics can be applied successfully to clinical orthodontics. Leaders in the field present comprehensive and cohesive guidance on orthodontic fundamentals, considerations in choosing orthodontic wire, treatment planning, and techniques for correcting a full range of conditions. Excellent line drawings and illustrations clarify important information, and an easy-to-follow format makes the book an ideal quick reference.
Keywords: Orthodontics; biomechanika; Biomechanical Phenomena; ortodoncie